Trade unionism in Austria and the Philippines the three significant points - Sarmiento, Manuel L. (Philippine Journal of Labor and Industrial Relations, 2005)
The essence of trade unionism is to secure for the workers the best price (Salary and wages) that can be obtained under prevailing market conditions. for the trade union to evolve into an economic, social and political force in the transformation of society, it must act deliberately as organizing centers of the working class in the broad interest of its complete emancipation. Towards this end, there must be a political party that will guide them in the pursuit of such role.